Adult Tissue Extracellular Matrix Determines Tissue Specification of Human iPSC‐Derived Embryonic Stage Mesodermal Precursor Cells - Ullah, Imran; Busch, Jonas Felix; Rabien, Anja; Ergün, Bettina; Stamm, Christof; Knosalla, Christoph; Hippenstiel, Stefan; Reinke, Petra; Kurtz, Andreas (Advanced science, 2020)
The selection of pluripotent stem cell (PSC)‐derived cells for tissue modeling and cell therapy will be influenced by their response to the tissue environment, including the extracellular matrix (ECM). Whether and how instructive memory is imprinted in adult ECM and able to impact on the tissue specific determination of human PSC‐derived developmentally fetal mesodermal precursor (P‐meso) cells is investigated. Decellularized ECM (dECM) is generated from human heart, kidney, and lung tissues and recellularized with P‐meso cells in a medium not containing any differentiation inducing components. While P‐meso cells on kidney dECM differentiate exclusively into nephronal cells, only beating clusters containing mature and immature cardiac cells form on heart dECM. No tissue‐specific differentiation of P‐meso cells is observed on endoderm‐derived lung dECM. P‐meso‐derived endothelial cells, however, are found on all dECM preparations independent of tissue origin. Clearance of heparan‐sulfate proteoglycans (HSPG) from dECM abolishes induction of tissue‐specific differentiation. It is concluded that HSPG‐bound factors on adult tissue‐derived ECM are essential and sufficient to induce tissue‐specific specification of uncommitted fetal stage precursor cells. The extracellular matrix holds tissue‐specific memory, which can trigger efficient tissue‐specific differentiation of lineage committed cells. Cues responsible for the specification are conserved throughout development and depend on the presence of heparan sulfate proteoglycans (HSPGs). Modulation of HSPG‐decorating factors can be utilized for matrix engineering.